Craniocervical Posture in Patients with Obstructive Sleep Apnea - Piccin,Chaiane Facco (2016)
Abstract Introduction Obstructive Sleep Apnea (OSA) is characterized by repeated episodes of upper airway obstruction during sleep. Objective The objective of this study is to verify the craniofacial characteristics and craniocervical posture of OSA and healthy subjects, determining possible relationships with the apnea/hypopnea index (AHI). Methods This case-control study evaluated 21 subjects with OSA, who comprised the OSA group (OSAG), and 21 healthy subjects, who constituted the control group (CG). Cephalometry analyzed head posture measurements, craniofacial measurements, and air space. Head posture was also assessed by means of photogrammetry. Results The groups were homogeneous regarding gender (12 men and 9 women in each group), age (OSAG = 41.86 11.26 years; GC = 41.19 11.20 years), and body mass index (OSAG = 25.65 2.46 kg/m2; CG = 24.72 3.01 kg/m2). We found significant differences between the groups, with lower average pharyngeal space and greater distance between the hyoid bone and the mandibular plane in OSAG, when compared with CG. A positive correlation was found between higher head hyperextension and head anteriorization, with greater severity of OSA as assessed by AHI. Conclusion OSAG subjects showed changes in craniofacial morphology, with lower average pharyngeal space and greater distance from the hyoid bone to the mandibular plane, as compared with healthy subjects. Moreover, in OSA subjects, the greater the severity of OSA, the greater the head hyperextension and anteriorization.